Bibliometric Analysis: Research on Green Supply Chain Management - Valent Krishna B; Nuryakin Nuryakin; Ika Nurul Qamari (Budapest International Research and Critics University, 2022)
Research on green supply chain management (GSCM) has recently become increasingly popular for every industry. The importance of this research has been examined in the area of green supply chain management (GSCM), trends in research, its authors and affiliates, and research possibilities for green supply chain management (GSCM). This study aims to describe forecasts related to the subject matter of the GSCM study, which will assess the performance of scientific journals with bibliometric analysis and also provide opportunities for Green Supply Chain Management (GSCM) studies. The data obtained from the Scopus database is metadata from the Green Supply Chain Management Journal (GSCM) 2015-2020 source. For data analysis purposes, all data information is transferred to CSV format, especially for VOSviewer data coincidence. There are up to 447 successful document metadata results articles. The study findings show that excavation is implementation dependent and SCM is the dominating subject in GSCM, while research on environmental performance and company achievement is the trend towards 2018. In this analysis, the analysis shows that excavation is dependent. GSCM research offers significant promise and prospects. Green supply chain management. Because it is easy to access several electronic data sources. Green Supply Chain Management (GSCM) is a field that has great opportunities for research to participate in the collaboration of various disciplines.